2013
DOI: 10.1007/s12185-013-1347-3
|View full text |Cite
|
Sign up to set email alerts
|

A role for RUNX1 in hematopoiesis and myeloid leukemia

Abstract: Since its discovery from a translocation in leukemias, the runt-related transcription factor 1/acute myelogenous leukemia-1 (RUNX1/AML1), which is widely expressed in hematopoietic cells, has been extensively studied. Many lines of evidence have shown that RUNX1 plays a critical role in regulating the development and precise maintenance of mammalian hematopoiesis. Studies using knockout mice have shown the importance of RUNX1 in a wide variety of hematopoietic cells, including hematopoietic stem cells and mega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 80 publications
4
81
0
Order By: Relevance
“…In fact, our findings demonstrated that PITHD1 functioned to regulate megakaryocyte differentiation by modulating RUNX1 expression. RUNX1 deficiency due to point mutation or translocation is one of most important genetic events leading to leukemia [4]. PITHD1 seemed to upregulate endogenous RUNX1 and antagonize the effect of dominant negative form of RUNX1, which mimics the inhibitory effect of RUNX1 genetic alterations found in leukemia, on PMA-induced megakaryocyte differentiation.…”
Section: Pithd1 Promotes Megakaryocyte Differentiation In Mouse Fetalmentioning
confidence: 93%
See 2 more Smart Citations
“…In fact, our findings demonstrated that PITHD1 functioned to regulate megakaryocyte differentiation by modulating RUNX1 expression. RUNX1 deficiency due to point mutation or translocation is one of most important genetic events leading to leukemia [4]. PITHD1 seemed to upregulate endogenous RUNX1 and antagonize the effect of dominant negative form of RUNX1, which mimics the inhibitory effect of RUNX1 genetic alterations found in leukemia, on PMA-induced megakaryocyte differentiation.…”
Section: Pithd1 Promotes Megakaryocyte Differentiation In Mouse Fetalmentioning
confidence: 93%
“…Runt-related transcription factor 1 (RUNX1) plays an important role in normal hematopoiesis and its deficiency or dysfunction due to mutations and translocation is one of frequent genetic alterations in leukemia [4]. It is required for embryonic HSC but not for definitive HSC function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, there are three RUNX genes: RUNX1, RUNX2 and RUNX3, each with distinct tissue specific expression patterns. RUNX1 is an extensively studied transcription factor which is well known in regulating development and maintenance of mammalian hematopoiesis and in translocation mediated leukemias' development (reviewed in [4]). Nevertheless, emerging functions of Runx1 in solid tumors have been recently shown.…”
Section: Saleh Khawaled and Rami I Aqeilanmentioning
confidence: 99%
“…Ts65Dn mice, which are trisomic for 104 orthologs of Hsa21 genes, display persistent macrocytosis and develop a myeloproliferative disease characterized by megakaryocyte hyperplasia and dysplasia, and myelofibrosis [19]. Several genes on Hsa21, such as RUNX1, ETS2, ERG, GAPBA, BACH1, and DYRK1A, encode proteins relating to hematopoiesis and leukemogenesis [9,[21][22][23][24][25][26]. Further analysis of the models may reveal the effect of chromosome 21 gene dosage on human hematopoiesis and hematological malignancies.…”
Section: Abnormal Hematopoiesis In Dsmentioning
confidence: 99%